Mutual Aid as a Strategy of Mobilization in a Colonial Context: The Case of Puerto Rico after 2017 (Altre Modernità, 2024)
Mutual Aid as a Strategy of Mobilization in a Colonial Context: The Case of Puerto Rico after 2017 by Ester Dazzo(Alma Mater Studiorum - Università di Bologna)SUPERVISOR: Prof. Alice Mattoni POSTGRADUATE DEGREE: MA in International Relations UNIVERSITY: Alma Mater Studiorum-Università di Bologna ACADEMIC YEAR: 2022-2023